Hubungan Efikasi Diri Akademik dengan Kesiapan Kerja Mahasiswa Tingkat Akhir pada Universitas X Surabaya - Mayya Kholishotus Sariroh; Jony Eko Yulianto (Psychopreneur Journal, 2018)
Senior students in University currently writing their thesis are facing with dilemmas, one of which is whether to find a career in a company. To find a job for senior students in university is not a piece of cake; the preparation is needed, both internally and externally. The preparation coming from within plays a significant role in terms of finding a job. Such preparation in terms of work readiness can be done through academic self efficacy. Students with high level of academic self efficacy also have high level in terms of work readiness. This study aims at carrying out the relation between academic self efficacy and work readiness of senior students in university. This study is a quantitative one using the design of correlational. The data were collected using the scale of academic self efficacy by Rachmawati (2015) and the work readiness scale by Caballero, Walker, & Fuller Tyszkiewicz (2011). The number of the respondents within the study is 194 students consisting of 88 male students and 104 female students in their senior year in their universities. Rank Spearman is employed in order to analyze the data. The result taken from the correlation test shows that the value of r = 0.747 and p = 0.000. It shows that the relation between academic self efficacy and the work readiness exists and is considered significant as the value of p < 0.05 and r > 0.3.